(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Background: Surgical Site Infection (SSI) is a less commonly encountered condition in Laparoscopic Cholecystectomy (LC). Whether prophylactic use of antibiotics in elective LC can reduce the incidence of SSI remains inconclusive. Prophylactic multiple dose antibiotic therapy after surgery is a common practice in our country to combat SSI. The study aimed to compare the incidence of SSIs after elective LC with single dose antibiotic and conventional multi doses prophylaxis antibiotic regimen. Materials and methods: This prospective randomized study was conducted during the period September 2019 to August 2020. A total of 100 patients who were admitted for elective LC in the Department of Surgery, Chittagong Medical College Hospital were included in this study. Patients were randomly allocated into two equal groups based on antibiotic prophylaxis: Single Dose Group (SDG) and Multiple Dose Group (MDG). SD group was given Cefuroxime axetil (750 mg) intravenously at the time of induction of anaesthesia and MD group was given Cefuroxime axetil (750 mg) intravenously at the time of induction of anaesthesia, followed by Cefuroxime (500 mg) orally twice daily for 7 days. Patients were followed up till 30th post-operative day to assess postoperative outcome in terms of SSI and other complications. Results: Both the groups were similar in terms of their demographic characteristics. The mean duration of postoperative hospital stay was 1.44±0.57 and 1.5±0.61 days in SDG and MDG, respectively. Grade I (Normal healing with mild bruising or erythema according to Southampton Wound Grading System) was found 3(6.0%) and 5(10.0%) in SDG and MDG, respectively (p=0.461). Conclusion: As there is no statistical difference between use of single dose antibiotic before and use routine multi doses antibiotic before and after elective LC, it could be concluded that preoperative single dose antibiotic is comparable to conventional multi doses prophylaxis antibiotic regimen in elective LC. Chatt Maa Shi Hosp Med Coll J; Vol.23 (1); January 2024; Page 34-37